2010
DOI: 10.1016/j.abb.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A new Factor Xa inhibitor from Amblyomma cajennense with a unique domain composition

Abstract: Bioactive compounds of great interest are found in the saliva of hematophagous organisms. While exploring a cDNA library derived from the salivary glands of the tick Amblyomma cajennense, a transcript that codes for a protein with unique structure (containing an N-terminal Kunitz-type domain and a C-terminus with no homology to any annotated sequences) was found. The recombinant mature form of this protein ( approximately 13.5kDa) was produced in Escherichia coli BL21 (DE3), and it was able to inhibit Factor X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 38 publications
1
54
0
7
Order By: Relevance
“…TAP, the Kunitz-type tick anticoagulant peptide from O. moubata (Waxman et al, 1990), the TAP-like protein from O. savignyi (Joubert et al, 1998), amblyomin-X from Amblyomma cajennense (Batista et al, 2010) and Salp14 (a basic tail-secreted protein) from I. scapularis (Narasimhan et al, 2002) are all inhibitors of coagulation factor Xa. Kunitz-type inhibitors that display similarity to the tissue factor (TF) pathway inhibitor have been identified, e.g., in I. scapularis (Ixolaris and penthalaris) (Francischetti et al, 2002, 2004), and Rhipicephalus hemaphysaloides (Rhipilin-1 and -2) (Gao et al, 2011; Cao et al, 2013).…”
Section: Tick Salivamentioning
confidence: 99%
“…TAP, the Kunitz-type tick anticoagulant peptide from O. moubata (Waxman et al, 1990), the TAP-like protein from O. savignyi (Joubert et al, 1998), amblyomin-X from Amblyomma cajennense (Batista et al, 2010) and Salp14 (a basic tail-secreted protein) from I. scapularis (Narasimhan et al, 2002) are all inhibitors of coagulation factor Xa. Kunitz-type inhibitors that display similarity to the tissue factor (TF) pathway inhibitor have been identified, e.g., in I. scapularis (Ixolaris and penthalaris) (Francischetti et al, 2002, 2004), and Rhipicephalus hemaphysaloides (Rhipilin-1 and -2) (Gao et al, 2011; Cao et al, 2013).…”
Section: Tick Salivamentioning
confidence: 99%
“…Amblyomin-X was initially discovered following SG transcriptome sequencing of the Amblyomma cajennense Cayenne tick (Batista et al, 2010). This protein harbors one Kunitz-type domain, and is observed in monomeric, dimeric, trimeric, and tetrameric conformations.…”
Section: Roles Of Serine Protease Inhibitors In Modulating Vertebratementioning
confidence: 99%
“…This protein harbors one Kunitz-type domain, and is observed in monomeric, dimeric, trimeric, and tetrameric conformations. Amblyomin-X inhibits FXa in a non-competitive manner but also increases PT and aPTT, suggesting an effect on prothrombin conversion (Batista et al, 2010; Branco et al, 2016). Four hypotheses have been proposed to explain the FXa inhibitory mechanism of Amblyomin-X.…”
Section: Roles Of Serine Protease Inhibitors In Modulating Vertebratementioning
confidence: 99%
See 1 more Smart Citation
“…It is a recombinant protein form (GenBank accession No. AAT68575) identified in the transcriptome of the salivary glands of the Amblyomma cajennense tick [14,15]. The studies performed with Amblyomin-X have shown that this is also able to induce cell cycle arrest and apoptosis in different tumor cell lines, and in vivo experiments, it promotes regression and reduction of metastases of some tested tumors [16,17].…”
Section: Introductionmentioning
confidence: 96%